Verificación del programa de puntos de inspección (PPI) ejecutado para la estructura metálica del nuevo puente sobre el río Virilla en la ruta nacional N° 147 - Quirós-Leiva, Juan Pablo (Instituto Tecnológico de Costa Rica, 2018)
In CONAVI, an Inspection Points Program’s verification is carried out on the metal structure that makes up the new bridge located on the Virilla River on National Route No. 147. CONAVI does not have advice on the processes of manufacture of metal structures, so it is important to confirm that the procedures performed by the contractor obey with the requirements of AWS D1.5 code and the work’s contract. This involves analyzing destructive and non-destructive tests in order to verify the quality of the supply steel and the welded joints of the structure, respectively. The test reports analyzed meet the quality standards of the mentioned code. The bridge material meets the desired strength, hardness and elongation requirements; while, the structure’s welds do not have major defects that may negatively affect the working conditions of the bridge.
Proyecto de Graduación (Bachillerato en Ingeniería de los Materiales con énfasis en Procesos Industriales) Instituto Tecnológico de Costa Rica, Escuela de Ciencias e Ingeniería de los Materiales, 2018.
Keywords: Verificación; Inspección; Estructura; AWS; Análisis; Research Subject Categories::TECHNOLOGY::Materials science::Construction materials